Sound-ring radiation of expanding vortex clusters - August Geelmuyden; Sebastian Erne; Sam Patrick; Carlo F. Barenghi; Silke Weinfurtner (Physical Review Research, 2022)
We investigate wave-vortex interaction emerging from an expanding compact vortex cluster in a two-dimensional Bose-Einstein condensate. We adapt techniques developed for compact gravitational objects to derive the characteristic modes of the wave-vortex interaction perturbatively around an effective vortex flow field. We demonstrate the existence of orbits or sound rings, in analogy to gravitational light rings, and compute the characteristic spectrum for the out-of-equilibrium vortex cluster. The spectrum obtained from numerical simulations of a stochastic Gross-Pitaevskii equation exhibiting an expanding vortex cluster is in excellent agreement with analytical predictions. Our findings are relevant for two-dimensional quantum turbulence, the semiclassical limit around fluid flows, and rotating compact objects exhibiting discrete circulation.